Risking: A Game for Teaching Risk Management in Software Projects - Santos, Sebastião; Carvalho, Flávia; Costa, Yandson; Viana, Davi; Rivero, Luis (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Risks in several categories such as: tasks, technology, people, among others, can affect the management of software development projects, since risky situations can occur in any type of project. Therefore, risk management is a vital activity that allows carrying out strategic planning that reduces the probability of occurrence and the negative impact of the risks, leading to the success of the project and the development of quality computer systems. Risk Management is one of the topics taught in introductory and advanced classes of software engineering, commonly addressed through lectures and case discussions. New learning objects, such as serious games, can also be applied to assist in teaching risk management. This paper presents the proposal of the game Risking (Arriscando in Portuguese), a card game that motivates the student to relate risks of software projects with possible solutions. To obtain empirical evidence regarding the learning and experience evoked by the game, we used the game in three software engineering classes. To evaluate the game, we applied the MEEGA+ questionnaire and a Focus Group dynamic. The results suggest that the game was well accepted, and that the students approved the dynamic used, the social interaction and the learning through an entertaining activity.